The incidence of subclinical forms of urogenital tuberculosis in patients with pulmonary tuberculosis. Issue 2 (March 2018) - Zachoval, Roman; Nencka, Petr; Vasakova, Martina; Kopecka, Emilie; Borovička, Vladimir; Wallenfels, Jiri; Cermak, Pavel
Abstract: The aim of our study was to determine whether patients with pulmonary tuberculosis may have subclinical forms of urogenital tuberculosis. Between 2011 and 2012, a prospective study was conducted. Basic demographic parameters were recorded and the following investigations were performed: direct bacilloscopy of sputum, evaluation of affected lung fields and presence of cavities on chest X-ray, Mantoux tuberculin skin test II, and interferon gamma release assay. Culture and molecular methods for Mycobacterium tuberculosis in urine were performed. In cases with a positive urine test, an ultrasound examination, computed tomography scan of the abdomen, and endoscopy of the urinary tract were performed. A total of 102 patients (75 men and 27 women) were included in the study, with a median age of 46.8 years. Subclinical forms of urogenital TB were detected in 7 patients; 5 by molecular methods, 1 by urine culture, and 1 with both methods The presence of subclinical forms of genitourinary TB was found in 4 patients without and 3 patients with findings on imaging methods corresponding to TB. A significant number of patients with pulmonary tuberculosis may simultaneously have subclinical forms of urogenital TB.